Job Changes and Hours Changes: Understanding the Path of Labor Supply Adjustment - Blundell, Richard; Brewer, Mike; Francesconi, Marco (Journal of Labor Economics, 2008)
We use British panel data to investigate single women’s labor supply changes in response to three reforms that affected individuals’ work incentives. We use these reforms to identify changes in labor supply. There is evidence of small hours of work effects for two of such reforms. A third reform in 1999 instead led to a significant increase in single mothers’ hours of work. The mechanism by which the labor supply adjustments were made occurred largely through job changes rather than hours changes with the same employer. This is little overall effect of the reforms on wages.